2020
DOI: 10.1002/ppul.25060
|View full text |Cite
|
Sign up to set email alerts
|

Parental attitude and knowledge towards asthma care measures for their children in Saudi Arabia

Abstract: Background: Appropriate asthma management in children reduces emergency department visits, hospitalization, and improves the quality of life. We aim to assess the level of children asthma control and its association with parental knowledge. Methods: A prospective study conducted to measure childhood asthma control with a validated childhood asthma control test (C-ACT), and to assess asthma knowledge among the parents of children aged 4-11 years and their parents upon asthma clinic visits. C-ACT score ≤ 19 is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…As observed by Ho et al [ 14 ], asthma knowledge is a multifaceted phenomenon, affected by complex sociodemographic and contextual factors, and the construction of a self-report asthma knowledge instrument to predict asthma outcomes may be an unfeasible task. Indeed, whereas some studies [ 3 , 4 , 5 , 6 ] reported an association between parental asthma knowledge and disease control as in our study, other studies did not [ 10 , 12 ]. This may also be ascribed to the general tendency of parents with poorer knowledge to underestimate the severity of asthma in their children and to report fewer symptoms [ 10 ].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…As observed by Ho et al [ 14 ], asthma knowledge is a multifaceted phenomenon, affected by complex sociodemographic and contextual factors, and the construction of a self-report asthma knowledge instrument to predict asthma outcomes may be an unfeasible task. Indeed, whereas some studies [ 3 , 4 , 5 , 6 ] reported an association between parental asthma knowledge and disease control as in our study, other studies did not [ 10 , 12 ]. This may also be ascribed to the general tendency of parents with poorer knowledge to underestimate the severity of asthma in their children and to report fewer symptoms [ 10 ].…”
Section: Discussioncontrasting
confidence: 85%
“…Current evidence shows that the parental level of asthma-related knowledge may influence asthma management practices [ 2 ] and affect children’s disease control [ 3 , 4 , 5 , 6 ]. Much of the existing literature studying the impact of parental knowledge on childhood asthma outcomes focuses on mothers as the primary caregivers [ 5 , 7 , 8 , 9 , 10 , 11 ], suggesting that asthma in children is majorly managed by mothers.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, a study from two major hospitals in Riyadh, which included 297 physician-diagnosed asthmatic children aged 3-11 years, found that 60.3% of the participants had uncontrolled asthma symptoms [ 28 ]. In 2020, two cross-sectional studies, one from Al Madinah Al Munawarah (n=278) [ 29 ] and the other from Riyadh (n=177), revealed that 62.6% and 61.6% of the participants were not adequately controlled, respectively [ 30 ]. Although our study showed less concerning figures, these observations from local studies indicate alarming levels of uncontrolled asthma among the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of adequate parental perceptions about asthma was more noticeable in another Saudi study (n=600), by Abu-Shaheen et al, where 53.5% of the respondents believed that asthma is solely a hereditary disorder, and 60.3% and 32% worried about the adverse effects of inhaled corticosteroids and the risk of drug dependency, respectively [ 33 ]. Moreover, Alhammad et al reported that a high percentage of parents were using asthma medications inadequately, as only 54.2% of the respondents were knowledgeable that salbutamol should be inhaled and only 37.9% knew the correct way to inhale corticosteroids [ 30 ]. Internationally, a recent systematic review of eight studies from different countries (three from Saudi Arabia) covering a total of 3,701 parents concluded that the levels of parental awareness and knowledge about asthma care are generally low [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation